Experiences of giving and receiving care in traumatic brain injury: An integrative review. Issue 7 (30th March 2018) - Kivunja, Stephen; River, Jo; Gullick, Janice
Abstract : Aims and objectives: To synthesise the literature on the experiences of giving or receiving care for traumatic brain injury for people with traumatic brain injury, their family members and nurses in hospital and rehabilitation settings. Background: Traumatic brain injury represents a major source of physical, social and economic burden. In the hospital setting, people with traumatic brain injury feel excluded from decision‐making processes and perceive impatient care. Families describe inadequate information and support for psychological distress. Nurses find the care of people with traumatic brain injury challenging particularly when experiencing heavy workloads. To date, a contemporary synthesis of the literature on people with traumatic brain injury, family and nurse experiences of traumatic brain injury care has not been conducted. Design: Integrative literature review. Methods: A systematic search strategy guided by the PRISMA statement was conducted in CINAHL, PubMed, Proquest, EMBASE and Google Scholar. Whittemore and Knafl's ( Journal of Advanced Nursing, 52, 2005, 546) integrative review framework guided data reduction, data display, data comparison and conclusion verification. Results: Across the three participant categories (people with traumatic brain injury/family members/nurses) and sixteen subcategories, six cross‐cutting themes emerged: seeking personhood, navigating challenging behaviour, valuing skills and competence, struggling with changed family responsibilities, maintaining productive partnerships and reflecting on workplace culture. Conclusions: Traumatic brain injury creates changes in physical, cognitive and emotional function that challenge known ways of being in the world for people. This alters relationship dynamics within families and requires a specific skill set among nurses. Relevance to clinical practice: Recommendations include the following: (i) formal inclusion of people with traumatic brain injury and families in care planning, (ii) routine risk screening for falls and challenging behaviour to ensure that controls are based on accurate assessment, (iii) formal orientation and training for novice nurses in the management of challenging behaviour, (iv) professional case management to guide access to services and funding and (v) personal skill development to optimise family functioning.